Towards a suicide-responsive police culture: police experiences of working with suicide - O'Reilly, Michelle (Policing and society, 2025)
Across the globe suicide rates are creating concern, and the World Health Organisation (WHO) argues that suicide is the responsibility of everyone. The WHO recognises that police have an important role in suicide prevention and the management of mental health crises. We suggest that police officers and staff are inevitably impacted by the emotional labour of meeting the demands of this aspect of the role. We argue for more research attention on the experiences and views of police who work with suicide. This study comprised qualitative reflective interviews with police in the UK, Guyana and New Zealand, with the focus on identifying commonalities in experience across the three locations. Four themes were generated through reflective thematic analysis: (1) the context; (2) the traumatic impact; (3) the difficult aspects of this work and (4) organisational opportunities for supporting police officers and staff. Our data illustrated that suicide is qualitatively different from other forms of death, and the nature of the work did have considerable emotional and traumatic impact on police. We conclude our paper with several recommendations for police forces to build their welfare support for staff. These recommendations could help promote a healthier workforce and recognise the specific issues associated with this part of the role.